Ocupación del timpo libre del adulto mayor de 65.80 años del hogar de ancianos San Sebastian en la ciudad de Riobamba año 2012-2013 - Paredes Godoy, Mercy Elizabeth (2013)
The research called leisure time SENIOR ADULT 65-80 years was conducted in the nursing home "SAN SEBASTIAN" IN THE YEAR 2012-2013 Riobamba, to solve the problem which is the misuse of free time in older adults, was raised under the next objective is to develop a physical activity plan - based recreational improve leisure time in adults aged 65 - 80 years of nursing home "Saint Sebastian" in the city Riobamba year 2012-2013, proposing the following variables that are a physical activity plan - recreation by taking time off following the conclusion; Old age is a stage of life full of fears, worries, anxieties, beliefs and myths; where communication with the other plays a key role in relations with the environment around them, every adult is different and has greater physical limitations, medical etc., a middle-aged participant, so we must adapt various activities like games, natural movements and exercises not so forced, we should avoid high-impact activities. This research was a population of 15 older adults, is participatory, consideration is also made a proposal entitled: HEALTHY LIVING IN THE ELDERLY NURSING HOME "St. Sebastian" Riobamba THROUGH RECREATION and do in their spare time.